Ultrasound-guided radiofrequency ablation for the treatment of anaplastic thyroid cancer: a case report - Liu, Tian; Xu, Chen; Chen, Hangjun; Chen, Fuhua; Feng, Bei; Tao, Xiaoying; Zhou, Yibo (Frontiers in Oncology, 2025)
BackgroundAnaplastic thyroid cancer (ATC) is a rare but highly aggressive tumor of the thyroid. Due to its rapid progression and resistance to radiotherapy, the prognosis of ATC is poor. Novel treatments have been increasingly applied in recent years, but the outcome of treatment is not satisfactory.Case presentationWe present a case of advanced ATC that cannot be surgically resected, who underwent ultrasound-guided radiofrequency ablation (RFA) combined with immunotherapy and targeted therapy for tumor shrinkage. The patient’s symptoms, including neck pain, were significantly relieved, and the follow-up of this patient showed a satisfactory outcome with no associated complications. To the best of our knowledge, this is the first case of palliative treatment by RFA in a patient with advanced ATC. It exemplifies a new application and success of this classical approach in palliative treatment.ConclusionThis case indicates that RFA has a good therapeutic effect on elderly patients with advanced ATC. Such an approach will provide new ideas for the treatment of advanced ATC and warrants further study in the future.